2009
DOI: 10.1179/136217108x341193
|View full text |Cite
|
Sign up to set email alerts
|

Solid state spot joining of sheet materials using consumable bit

Abstract: A new spot joining technology relying on a consumable joining bit has been developed and evaluated on dual phase (DP) 980 steel and a dissimilar combination of aluminium alloy 5754-O and DP 980. This new process, called friction bit joining (FBJ), uses a consumable bit to create a solid state joint in sheet materials by the action of cutting and frictional bonding. FBJ lap shear fracture loads were 14?7 kN for 1?4 mm DP 980 compared to 16?6 kN for RSW, for the same spot diameters. FBJ of a dissimilar combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…The shape of the tip of the joining bit is also placed in Figure 1(a). Miles et al [23] have shown the feasibility of this process for joining of steel/steel and aluminum/steel and have demonstrated the high level of lap shear strength of the joints. They showed the high potential of FBJ as a new spot welding process, e.g., the higher strength in the dissimilar friction bit joint between steel and aluminum.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The shape of the tip of the joining bit is also placed in Figure 1(a). Miles et al [23] have shown the feasibility of this process for joining of steel/steel and aluminum/steel and have demonstrated the high level of lap shear strength of the joints. They showed the high potential of FBJ as a new spot welding process, e.g., the higher strength in the dissimilar friction bit joint between steel and aluminum.…”
Section: Introductionmentioning
confidence: 96%
“…[23] This concept relies on a cutting step, where the bit cuts through the top layer (or layers) of material, followed by a joining step where the bit and surrounding sheet materials are heated by friction and where the bit is consumed as filler material that joins the sheets together. At the end of the joining process, the spindle of the welding machine was stopped and then restarted to separate the joining bit from the weld.…”
Section: Introductionmentioning
confidence: 99%
“…The principle is for the rotating bit to cut through the Al top sheet and then engage the steel bottom sheet. Frictional heat creates a diffusion bond between the joining bit and steel bottom workpiece whereupon the spindle is stopped suddenly similar to inertia drive welding [153]. The rotation of the steel bit results in alternating bands of bit material and steel bottom workpiece material [102] similar to what is observed in friction stir welds of dissimilar alloys.…”
Section: Friction Bit Joiningmentioning
confidence: 48%
“…Han and Chrysanthou [3] joined aluminum alloy and high strength steel using self-piercing riveting. Based on these studies, a new joining method, termed friction bit joining, has been developed for spot joining of dissimilar metal alloys [4]. Another novel spot joining method, fiction stir spot welding, has been used recently to join aluminum alloy sheet and steel sheet [5].…”
Section: Introductionmentioning
confidence: 99%